Samorealizacja życiowa osób z niepełnosprawnością - Jachimczak, Beata (Wydawnictwo Naukowe UAM, 2013)
The problem of self-fulfi lment is the area of interest for many scientifi c disciplines; considerations and questions concerning its defi nition and conditions are present in psychological, educational, philosophical, and theological publications. Also, in the fi eld of special education, the ideas for supporting self-development of people with disabilities are still the subject of scientifi c inquiry and research. Given the fact that formal education (which in fact takes up about ¼ of human lifespan) can and should be a time for self-discovery, becoming independent and changing self-image, I decided that it is worth searching for the answer to the question of what education meant for people with learning disabilities in the context of self-fulfi lment and a sense of life satisfaction.
Self-fulfilment of People With Disabilities
Keywords: person with a disability; self-fulfi lment